(untitled) - Arreola-Risa, Antonio; Keys, Barry (Business Expert Press, 2013)
Ebook from IG Library ; Because supply chains themselves in recent years have become a source of sustainable competitive advantage, they are a topic of great interest to business professionals. While the literature on supply-chain management is extensive, the same cannot be said for supply-chain design in general and R&D supply chains in particular.
Keywords: Quản trị chuỗi cung ứng; Supply and Operations Management